Diel activity rhythm in Callinectes ornatus Ordway, 1863 and Callinectes danae Smith, 1869 (brachyura, portunidae) under laboratory conditions - Reigada, ALD (Kluwer Academic/plenum Publ, 2002)
The locomotory and feeding activity rhythms of Callinectes ornatus Ordway, 1863 and Callinectes danae Smith, 1869 were examined under laboratory conditions. Light significantly influenced the activity of these organisms. However, activity in both species was affected by the presence of food, independently of photoperiod regime.